A Systematic Review of the Association Between Intrapersonal Factors and Smoking Cessation in Adolescents in the United States - Hana, Amanita K; Cho, Sung-il; Cheon, Eunsil; Kwon, Suhyun; Thishani, Rajapakshe (UI Scholars Hub, 2018)
Background: Premature death in developed countries, and smoking by adolescents is a serious health issue in the US. There are several aspects that influence smoking cessation in adolescents, one of which comprises intrapersonal factors. The aim of this systematic review was therefore to identify and categorize specific intrapersonal factors that affect the smoking cessation of adolescents in the United States. Methods: Through a search on PubMed, identified quantitative research studies on the intrapersonal factors affecting the smoking cessation of adolescents in the US. The search results imported into Endnote X9. The intrapersonal factors examined into 4 classifications: nicotine dependence, stress, related beliefs, and other emotional factors. Each study's bias was assessed using RoBAN and RevMan 5. Results: The sample sizes ranged from 66 to 975 participants, with an age range of 12-21 years. 7 studies were classified as covering nicotine dependence, 2 studies as covering other emotional factors, 1 study was classified as covering related beliefs, and 1 study was classified as covering stress. Conclusions: Nicotine dependency was found to have the highest incidence among all the contributing factors. Stress and other emotional factors were found to stem from depression and low emotional control.